TRANSFORMASI NILAI-NILAI EKONOMI ISLAM DALAM MEWUJUDKAN KEADILAN DISTRIBUTIF BAGI PENGUATAN USAHA KECIL MIKRO DI INDONESIA - Euis Amalia (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2011)
Distributive unfairness still appears in various aspects including government budget allocation policies in an attempt to develop a small micro entrepreneurs, either through the State Budget (APBN) and the allocation of bank financing to SMEs. The policies put forward the interests of big business are only owned by a handful of people. Whereas the majority of Indonesian people are in the small micro entepreneurs. Economic values of Islam inthis article attempted to be transformed in a number of policies and efforts of the stakeholders to implement the instruments of Islamic economics, free of ribâ, and put zakâh as the main tool of redistribution budgetDOI: 10.15408/aiq.v3i1.2497